Cardiac magnetic resonance-derived fibrosis, strain and molecular biomarkers of fibrosis in hypertensive heart disease. Issue 10 (October 2020) - Pichler, Gernot; Redon, Josep; Martínez, Fernando; Solaz, Elena; Calaforra, Oscar; Andrés, Marta San; Lopez, Begoña; Díez, Javier; Oberbauer, Rainer; Adlbrecht, Christopher; Karth, Georg Delle; Maceira, Alicia
Abstract : Aims: Myocardial fibrosis is a relevant component of hypertensive heart disease (HHD). Novel cardiovascular magnetic resonance (CMR) imaging techniques have shown potential in quantification of diffuse cardiac fibrosis, with T1 mapping, and estimating preclinical cardiac dysfunction, with strain analysis. Molecular biomarkers of fibrosis have been related with clinical outcomes and histologically proven myocardial fibrosis. The relationship between these CMR-imaging techniques and circulating biomarkers is not fully understood. Methods and results: CMR was performed on a 3T scanner in 36 individuals with HHD. Extracellular volume fraction (ECV) and the partition coefficient were assessed using the T1 mapping technique shMOLLI. Longitudinal, circumferential and radial strain was assessed using CMR-Feature Tracking. Molecular biomarkers of collagen synthesis (PICP and PIIINP) and collagen degradation (CITP and MMP-1) were measured in blood using commercial kits. Correlation models showed a significant relationship of T1 mapping measures with left atrial diameter, LV mass, LV posterior wall thickness, LV end-diastolic volume and longitudinal strain. In fully adjusted regression models, ECV was associated with left atrial diameter ( β =0.75, P = 0.005) and longitudinal strain ( β = 0.43, P = 0.030); the partition coefficient was associated with LV posterior wall thickness ( β = 0.53, P = 0.046). Strain measures were associated with cardiac geometry, and longitudinal strain was marginally associated with CITP. Conclusion: In individuals with HHD, CMR-derived measures of myocardial fibrosis and function are related and might be useful tools for the identification and characterization of preclinical cardiac dysfunction and diffuse myocardial fibrosis. Molecular biomarkers of fibrosis were marginally associated with myocardial strain, but not with the extension of CMR-measured cardiac fibrosis. Abstract : Supplemental Digital Content is available in the text